How New Green Technologies are Changing the Indonesian Economy - Bella Jastacia; Sun Yonglei (Pusbindiklatren Bappenas, 2023)
Rapid disruption simplifies company performance improvement. Instead, businesses must be conscious of environmental risks. Innovation in green technology is a business strategy for preventing environmental damage. However, few studies have investigated the internal mechanisms and underlying factors that link ecological innovation to corporate financial performance. The methodology of this research used content analysis to examine companies listed on the IDX in the manufacturing sector with heavy pollution. In addition, it is important to learn that developing more eco-friendly processes and merchandise can boost a business's bottom line. In addition, the company's green reputation could mitigate the effects of innovative green products and new green processes on the bottom line. The results can provide valuable input and recommendations for effectively implementing green technology in Indonesia.